2018
DOI: 10.1177/2050312118801707
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival with continuation of statins in bacteremic patients

Abstract: Objectives:Varying statin exposures in bacteremic patients have different impacts on mortality. Among patients with adherent statin use, we sought to evaluate the impact of statin continuation on inpatient mortality in bacteremic patients.Methods:A retrospective cohort study was conducted using Optum ClinformaticsTM with matched Premier Hospital data (October 2009–March 2013). Patients with a primary diagnosis of bacteremia and 6 months of continuous enrollment prior to the admission, receiving antibiotics at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The anti-inflammatory properties were independent of the lipid-lowering abilities of the statins. We did not evaluate the influence of statins on the course of infection, but almost all patients with hyperlipidaemia and atherosclerosis took them [ 37 , 38 , 39 , 40 , 41 ]. Statins may have resulted in a lower frequency of infections in patients with atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory properties were independent of the lipid-lowering abilities of the statins. We did not evaluate the influence of statins on the course of infection, but almost all patients with hyperlipidaemia and atherosclerosis took them [ 37 , 38 , 39 , 40 , 41 ]. Statins may have resulted in a lower frequency of infections in patients with atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Pawar et al (Pawar et al, 2018) found that continued statins use for at least two days after admission provided a survival benefit among bacteremia patients. Similar to our study, about 77% (21/91) of patients continued using statins for more than two days.…”
Section: Discussionmentioning
confidence: 99%